Subjectivities in Software Development from an STS and Social Institution Perspective, a Riot Games Case Study - Carvalho, Luiz Paulo; Oliveira, Jonice (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES), 2020)
We are influenced and influence Social Institutions, which shape our subjectivities and, consequently, our actions, such as software engineering. In this work, we use a socio technical perspective to study and analyze the interrelation between the dimensions of an Information System, Social Institutions, and subjectivities, applied in the software company Riot Games. We develop a perception of co conducting culture and values between the requirements of an artifact and its other dimensions, for example, through organizational culture, habits, codes of conduct, among others.